THE INFLUENCE OF INTERNAL AUDIT AND WHISTLEBLOWING SYSTEM EFFECTIVENESS ON FRAUD PREVENTION - Justinia Castellani; Anggita Nuralisa (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
This research aims at finding out and analyzing how much influence internal audit and whistleblowing system effectiveness had on fraud prevention at rural banks (BPR) in Bandung Regency. The sample of this research used an internal auditor who worked at a rural bank in Bandung Regency. The results of simple linear regression data processing showed that the effectiveness of internal audit and whistleblowing system can prevent fraud.